S The Curriculum Management Strategy for Extracurricular Activities in Enhancing School Achievement at SMPN 1 Gondangwetan, Pasuruan Regency - Sari, Dian Puspita; Suyanto, Suyanto; Wahyudi, Furqon (The Future of Education Journal, 2026)
Currently, education must be able to face the dynamics of 21st-century development, which is full of challenges. This can be achieved through extracurricular activities. These activities are also an integral part of the school curriculum. Through extracurricular activities, students not only achieve academic success but also non-academic accomplishments. This study aims to describe the curriculum management strategy for extracurricular activities in enhancing school achievement. The research uses a descriptive qualitative approach and was conducted at SMPN 1 Gondangwetan, Pasuruan Regency. Data collection techniques include in-depth interviews, participatory observation, and document study, involving the school principal, vice principal for student affairs, extracurricular coordinators, and students. Data validity is ensured through source and technique triangulation, while data analysis is carried out through the stages of data reduction, data presentation, and conclusion drawing. The results show that an effective extracurricular curriculum management strategy includes planning aligned with the school's vision, clear task division, collaborative activity implementation, and ongoing evaluation based on student achievement outcomes. This strategy has an impact on the improvement of school achievement.